(untitled) (Constructionism Conference Proceedings, 2025)
The subject of this research is the study of students’ collaboration on the debugging and production of digital models, within the programming environment MaLT2, to examine how collaboratively engaging with transformative technologies redefines learning, affects the production, expression and communication of ideas and how it enriches mental constructions and connections between abstract mathematical ideas and concrete programming implementations. This is an empirical study addressed to 9th grade students and consists of a series of exploratory activities assigning children the active role of ‘co-creators’ and creative tinkerers of digital artefacts, working in a community of practice with digital tools.